Subsequent gene expression pattern in dendritic cells following multiple trauma - Geiger, Emanuel Valentin; Maier, Marcus; Schiessling, Serin; Wutzler, Sebastian; Lehnert, Mark; Marzi, Ingo; Henrich, Dirk (Langenbeck's archives of surgery, 2013)
Major trauma initiates a systemic inflammatory response, which is characterized by systemic release of various chemokines. There is growing evidence for the extraordinary role of dendritic cells (DC) as professional antigen-presenting cells and activators of the immune response. Recently, the impact of severe trauma on DC transcriptomic activation was demonstrated. The purpose of the present study was to evaluate gene expression pattern in DC following multiple trauma to gain further understanding of the mechanisms of posttraumatic immune response.
Gesehen am 03.02.2020
First published: 22 November 2012